The courtyards of the house of the Lord : studies on the Temple scroll - Schiffman, Lawrence H. (Studies on the Texts of the Desert of Judah, 2008)
Already before its publication, it was clear that the Temple Scroll represented a major contribution to the history of Jewish law in Late Antiquity. The present volume brings together the author's studies on this important scroll. He has sought to uncover the hermeneutics of the Zadokite/Sadducean legal system and to compare and contrast it with other texts of its own type as well as with those in rabbinic literature preserving the Pharisaic-rabbinic approach.